Abu Nawas Sabah Folk Version: Intertextuality and Creativity: (Abu Nawas Versi Rakyat Sabah: Intertekstualiti dan Kreativiti) (Malay Literature, 2015)
The tales of Abu Nawas, which originated in Arab-Persia are popular humorous stories told in the Malay world. Several written sources reveal that these tales spread to the Malay world between the 13th and 15th centuries, through the books One Thousand and One Nights and Hikayat Abu Nawas. Drawing from field trips conducted in a number of places in Sabah, a total of 13 tales, that had been transmitted orally among Sabah indigenous informants, have been collected. Upon comparison with Hikayat Abu Nawas, it was found that some of the Sabah folk version of Abu Nawas tales are similar to those published in Hikayat Abu Nawas while some are very different. This study attempts to compare the motifs of the original Abu Nawas tales with those of the Sabah folk version based on the principles of intertextuality. The intertextual comparison shows that early on, the indigenous people of Sabah had been exposed to the Abu Nawas stories. Later however, the stories were retold based on local elements. In the end, the indigenous storytellers of Sabah began to create their own version with motifs different from that of the original tales. These retold stories are rich in local color and motifs, highlighting the genius and creativity of local Sabah storytellers.Keywords: Abu Nawas, humorous tale, intertextuality, motif comparison, local genius, creativity